PENINGKATAN KUALITAS PEMBELAJARAN STUDI KELAYAKAN BISNIS MELALUI METODE LEARNING CYCLE - Hadi, Syamsu (Dinamika Pendidikan, 2009)
The objectives of the study are to improve the quality of learning for Studi Kelayakan Bisnis (Business Feasibility Study), to improve studentsÃ¢â¬â¢ spirit in learning, to improve lecturersÃ¢â¬â¢ skill in developing learning model and media andÃÂ  also to improve studentsÃ¢â¬â¢ achievement in learning. This study was class action research consists of three cycles. Result of study showed studentsÃ¢â¬â¢ achievement was improving on each cycle. StudentsÃ¢â¬â¢ learning completeness before applying Learning Cycle method was 0%, after applying Learning Cycle method; studentsÃ¢â¬â¢ achievement after final test was 94%. StudentsÃ¢â¬â¢ interest, activeness and relationship in learning process with range 1-4, the result was good (3.2). Result of observation related to lecturersÃ¢â¬â¢ skill in managing the learning process which used map concept method with range 1-4 showed a good result with average of cycle 1, cycle 2 and cycle 3 was 3.2. That score was the average of all aspects investigated on three cycles. Based on result of study, it was suggested that for lecturers of Business Feasibility Study subject to apply Learning Cycle method in teaching-learning process. This method was approved to improve studentsÃ¢â¬â¢ ability to analyze the case and understand the concepts of Business Feasibility Study. This was because students are given opportunity to do research in the field related to the topic and then find the problems that will be discussed in the class. Thus, students are usual to think critically and analytically to face a case. And finally, students can find the topics concepts. Moreover, result of study can be applied for other subjects because this study gives the positive impact. Key words: The Quality of Learning, Business Feasibility Study Subject, LearningCycle Method